Kajian Waktu Penyelesaian Metode Crane Dan Metode Launcher Dalam Pelaksanaan Erection Girder Jembatan (Studi Kasus : Pembangunan Jalan Tol Semarang – Solo Ruas Salatiga – Boyolali Sta 40+409 – Sta 71+785) - Farouq Khoirul Izza; Muhammad Ariya Praditama; Claudia Nimas Kirana; Karnawan Joko Setyono; Sudarmono Sudarmono (Politeknik Negeri Semarang, 2019)
The Semarang-Solo Toll Road Project for the Salatiga-Kartasura Section is one part of the Trans Java toll road development project, one of the jobs in the form of an erection girder with the method used, namely the Crane and Launcher methods. The purpose of this study is to compare the completion time between Crane and Launcher Methods with field studies and analysis. Stages of research include literature studies, primary data collection in the form of variable time of completion and secondary data then analyzed by comparing the completion time of the second method of erection girder on girder with a span of 20.8 meters and 40.8 meters. The results of the comparison of completion time were obtained on a 20.8 meter span erection girder seen from the shortest time Crane Method was more efficient 61.44% than the Launcher Method, the longest time Crane Method was more efficient 32.13% of the Launcher Method, and Method average time Crane is more efficient 52.15% than the Launcher Method. Then on the span erection girder 40.8 m seen from the shortest time Crane Method is more efficient 61.48% than the Launcher Method, the longest time Crane Method is more efficient 29.82% than the Launcher Method, and the average time of the Crane Method is more efficient 41, 81% of the Launcher Method.